Mixed language dominance: insights from a case of unexpected fluent aphasia with semantic jargon resulting from massive left perisylvian lesion. Issue 1 (2nd January 2018) - Kasselimis, Dimitrios; Potagas, Constantin; Simos, Panagiotis; Evdokimidis, Ioannis; Whitaker, Harry
ABSTRACT: We report a right-handed patient with a massive lesion in left perisylvian language cortex, who unexpectedly presented with fluent aphasia with semantic jargon. Language deficits were assessed with a comprehensive battery of language tests. Comprehension, naming, reading, and writing were severely impaired, and verbal expression was moderately fluent with semantic jargon. Although the patient's lesion included brain areas typically essential for motor speech coordination, he was neither nonfluent nor apraxic. He exhibited strikingly unexpected aphasia with semantic jargon and prominent comprehension deficits, suggesting that this is a case of mixed dominance: the right hemisphere likely controls motor speech and basic syntactic skills, while the severely damaged left hemisphere controls semantic processing, predictably severely impaired.